New Testament Greek manuscripts : Luke varient readings arranged in horizontal lines against Codex Vaticanus - Swanson, Reuben Joseph (Sheffield, UK Sheffield Academic, 1995)
Includes bibliographical references.
Keywords: Bible. N.T. Luke -- Greek Texts; Bible. N.T. Luke -- Codex Vaticanus